Catalysis with Supported Size-selected Pt Clusters Fundamental UHV and Applied Ambient Experiments - Schweinberger, Florian Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
In his thesis, Florian Schweinberger investigates the influence of the precise size of catalytically active species on reactivity. In order to do this he carries out studies both in UHV and under ambient conditions for supported, size-selected Platium clusters (8-68 atoms). Schweinberger probed the electronic structure, adsorption properties and reactivity of two olefins on surfaces and Pt clusters in the submonolayer range. With adsorbed trichloroethene (TCE) a possible cluster-adsorbate induced change in the electronic structure, and for ethene a low-temperature, size-dependent self-/hydrogenation was observed.In a collaborative approach, Schweinberger and colleagues investigated Pt clusters under ambient pressure conditions. They characterised the clusters at at the local and integral level and tested for temperature stability. Experiments in gas phase ?-reactors and in liquid, as part of a hybrid photocatalytic system, revealed size-dependent reactivity.Overall this thesis is not only of interest for those who want to perform similar experiments but also provides superb scientific insights for researchers in the field.
Introduction -- Background and methods -- Literature survey and theory -- Experimental methods -- Ultra high vacuum -- Model catalysts under vacuum conditions -- Ambient -- Cluster catalysts under applied conditions -- Conclusion and outlook.
Keywords: Chemistry; Chemistry, Physical organic; Catalysis; Renewable energy sources; Chemistry; Catalysis; Physical Chemistry; Renewable and Green Energy